Wyniki ekonomiczne klubów sportowych o statusie pożytku publicznego w Polsce = Economic performance of sports clubs charitable status in Poland - Wyszyński, Artur (Journal of Education, Health and Sport, 2015)
Wyszyński A. Wyniki ekonomiczne klubów sportowych o statusie pożytku publicznego w Polsce = Economic performance of sports clubs charitable status in Poland. Journal of Education, Health and Sport. 2015;5(11):466-480. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35676 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A466-480 http://pbn.nauka.gov.pl/works/684701 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Original Text published © The Author (s) 2015. Wyszyński A. Wyniki ekonomiczne klubów sportowych o statusie pożytku publicznego w Polsce. Quality in Sport. 2015;1(1):7-20. eISSN 2450-3118. http://ojs.ukw.edu.pl/index.php/QiS/article/view/QUALITY%20IN%20SPORT%201%20%281%29%202015%2C%20s.%207-20 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015. Artur Wyszyński[1] Katedra Finansów i Bankowości, Wydział Nauk Ekonomicznych, Uniwersytet Warmińsko-Mazurski w Olsztynie Wyniki ekonomiczne klubów sportowych o statusie pożytku publicznego w Polsce Economic performance of sports clubs charitable status in Poland Streszczenie Głównym celem artykułu jest ocena kondycji i wyników finansowych polskich klubów piłkarskich mających status organizacji pożytku publicznego (OPP). Analizę przeprowadzono dla klubów, które rozgrywały mecze w sezonie 2013/2014 w rozgrywkach męskiej piłki nożnej na wszystkich szczeblach rozgrywek oprócz najwyższej tj. Ekstraklasy (brak klubów mających status OPP) na szczeblach: I, II, III, IV ligi oraz klasy okręgowej, A, B i C. Wszystkie kluby poddane analizie funkcjonują jako stowarzyszenia. Na podstawie przeprowadzonej analizy wynika, że kluby znajdują się w złej sytuacji finansowej. Większość klubów, niezależnie od poziomu klasy w jakiej rozgrywały mecze charakteryzowały się niską wartością zasobów majątkowych. Średnie zadłużenie było bliskie 100%. W rezultacie blisko jedna trzecia klubów wykazała ujemną wartość kapitału własnego. U blisko połowy klubów obserwowano ujemną wartość rentowności majątku ogółem oraz rentowności sprzedaży. W strukturze przychodów podstawowym źródłem są środki publiczne. Do innych źródeł przychodów klubów zaliczono środki prywatne, pozostałe oraz przychody z 1% podatku od osób fizycznych. Słowa kluczowe: klub sportowy, analiza finansowa, przychody klubów piłkarskich Abstract The main aim of this article is to assess the financial condition and results of Polish football clubs who have the status of public benefit organizations (OPP). The analysis was conducted for clubs that were played matches in the 2013/2014 season in the men’s football tournament at all levels except the highest such competitions. Ekstraklasa (no clubs having the status OPP) for levels I, II, III, IV league and class district, A , B and C. All the clubs analyzed as a function of the association. The analysis shows that clubs are in a bad financial situation. Most clubs, regardless of the grade level in which the matches were played were characterized by a low value of wealth. Average debt was close to 100%. As a result, nearly one-third of the clubs showed a negative equity value. About half of the clubs observed a negative value total return on assets and return on sales. In the structure of revenues are the primary source of public funds. Other sources of income included clubs, private funds, other and income from the 1% tax on individuals. Key words: club sports, financial analysis, income football clubs [1] e-mail artur.wyszynski@uwm.edu.pl